Structural studies and selected physical investigations of LiCoO2 obtained by combustion synthesis - Michalska, Monika; Ławniczak, Paweł; Strachowski, Tomasz; Ostrowski, Adam; Bednarski, Waldemar (Beilstein Journal of Nanotechnology, 2022)
Nanocrystalline powders of LiCoO2 were synthesized using a modified solution combustion method, and the effects of the annealing temperature (450–900 °C) on structure and composition were investigated using various methods, including XRD, SEM, EPR, and electrical studies. It was found that, as the process temperature increases, the value of the specific surface area decreases, and, hence, the size of the crystallites increases. XRD analysis showed that phase-pure LiCoO2 material was maintained without additional phases. EPR studies revealed the presence of two Ni3+ complexes resulting from Ni impurities. The electrical properties of the studied LiCoO2 samples were investigated by using impedance spectroscopy. Comparison of the effect of annealing temperature on electrical conductivity shows a very interesting behavior. As the annealing temperature increases, the DC conductivity value increases, reaching a maximum at a temperature of 500 °C. However, further increase in the annealing temperature causes a steady decrease in the DC conductivity.
Keywords: lithium cobalt oxide; lithium-ion battery; nanocrystalline powder; solution combustion synthesis